2014
DOI: 10.1099/mic.0.080689-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of the yakA gene in morphogenesis and stress response in Penicillium marneffei

Abstract: Penicillium marneffei is a thermally dimorphic fungus and a highly significant pathogen of immunocompromised individuals living in or having travelled in south-east Asia. At 25 6C, P. marneffei grows filamentously. Under the appropriate conditions, these filaments (hyphae) produce conidiophores bearing chains of conidia. Yet, when incubated at 37 6C, or upon infecting host tissue, P. marneffei grows as a yeast that divides by binary fission. Previously, an Agrobacteriummediated transformation system was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Thus, as had been seen for other thermally dimorphic fungus, T. cutaneum B3 also showed morphological switch that was related to the temperature of cultivation. But the relationship between dimorphic transition and temperature of cultivation in T. cutaneum was the reverse of that described by Penicillium marneffei [53] and Blastomyces dermatitidis [54].…”
Section: Dimorphic Transition In T Cutaneum Is Reversiblementioning
confidence: 76%
“…Thus, as had been seen for other thermally dimorphic fungus, T. cutaneum B3 also showed morphological switch that was related to the temperature of cultivation. But the relationship between dimorphic transition and temperature of cultivation in T. cutaneum was the reverse of that described by Penicillium marneffei [53] and Blastomyces dermatitidis [54].…”
Section: Dimorphic Transition In T Cutaneum Is Reversiblementioning
confidence: 76%
“…Moreover, it has been reported that Yak1 is involved in the initiation and maintenance of hyphal growth in Candida albicans (Goyard et al, 2008). Similar to S. cerevisiae Yak1, involvement of Yak1 orthologue in stress response in Penicillium marrneffei has been also reported (Suwunnakorn et al, 2014). Unlike Yak1, Sch9 is one of the AGC (protein kinase A, G, or C) kinases which is structurally related to the catalytic subunits of PKA.…”
Section: Introductionmentioning
confidence: 91%
“…The C. albicans yak1‐ null mutant exhibits defects in yeast‐to‐hypha transition, maintaining hyphal growth and biofilm formation but remains virulent in animal models (Goyard et al ., ). The yakA mutant of Penicillium marneffei is defective in conidiation, conidial germination and cell wall integrity (Suwunnakorn et al ., ). The Fusarium graminearum knockout mutant for Yak1 is normal in vegetative growth, but exhibits defects in conidiation, disease development and stress response (Wang et al ., ).…”
Section: Introductionmentioning
confidence: 97%